Comparison of 6 different gutta-percha techniques (part II): Thermatil, JS quick-fill, soft core, microseal, system B, and lateral condensation - (:unkn) unknown (MOSBY, INC, 2003)
Objectives. In this in vitro study, the core-to-sealer ratios were calculated for 6 different gutta-percha techniques: Thermafil, JS Quick-Fill, Soft Core, Microseal, System 13, and lateral condensation. The core consisted of gutta-percha or gutta-percha and carrier. Study design. The sealer-to-core ratios for the Thermafil, JS Quick-Fill, System 13, and lateral condensation techniques were published previously. In this study, the sealer-to-core ratio for Microseal and Soft Core techniques was investigated. For this purpose, 20 teeth filled by using the Soft Core or the Microseal technique were embedded in resin and sectioned horizontally at 1, 2, 3, and 4 mm from the anatomic apex. Photographs were taken of each section, and the total area of the canals filled with core material or sealer was calculated. Results. Once all results were compiled, it became clear that core techniques (Thermafil, JS Quick-Fill, and Soft Core) produced higher gutta-percha content than the Microseal, System B, and lateral condensation techniques (P <.05). The lateral condensation technique produced the least gutta-percha content (P <.05). Conclusion. Thermafil, JS Quick-Fill, and Soft Core were found to be superior to the Microseal, System 13, and lateral condensation techniques in terms of the gutta-percha-to-sealer ratio.
Keywords: ROOT-CANAL SEALERS; TERM SEALING ABILITY; OBTURATION TECHNIQUES; SMEAR LAYER; APICAL MICROLEAKAGE; ABSENCE; SOLUBILITY; ADAPTATION; LEAKAGE; PASTES